Assessing asymptotic tail independence: a simulation study † - Ferreira, Marta Susana (2024)
The occurrence of extreme values in one variable can trigger the same in other variables, making it necessary to assess the risk of contagion. The usual dependence measures based on the central part of the data typically fail to assess extreme dependence. Within the scope of EVT, tail dependence measures were developed, such as the Ledford and Tawn coefficient that we discuss here. This is a measure of residual dependence that is particularly important when it comes to analyzing at the tail level where data are scarce. We will consider different estimation methodologies and compare them based on a simulation study. We finish with an application to real data.